Effects of Acute Hypoxic Exposure in Simulated Altitude in Healthy Adults on Cognitive Performance: A Systematic Review and Meta-Analysis - María Ramírez-delaCruz; Alfredo Bravo-Sánchez; Jorge Sánchez-Infante; Pablo Abián; Javier Abián-Vicén (Biology)
The neurocognitive response following hypoxia has received special interest. However, it is necessary to understand the impact of acute hypoxic exposure induced by simulated altitude on cognitive performance. This study aimed to determine the effects of acute hypoxic exposure in simulated altitude in healthy adults on reaction time, response accuracy, memory, and attention. Five electronic databases were searched. The inclusion criteria were: (1) Experimental studies involving a hypoxia intervention induced by a hypoxic air generator to determine the effects on cognitive performance; and (2) Conducted in adults (males and/or females; aged 18–50 years) without pathologies or health/mental problems. Four meta-analyses were performed: (1) reaction time, (2) response accuracy, (3) memory, and (4) attention. Finally, 37 studies were included in the meta-analysis. Hypoxia exposure induced detrimental effects on reaction time (standard mean difference (SMD) −0.23; 95% confidence interval (CI) −0.38–−0.07; p = 0.004), response accuracy (SMD −0.20; 95% CI −0.38–−0.03; p = 0.02), and memory (SMD −0.93; 95% CI: −1.68–−0.17; p = 0.02). Nevertheless, attention was not affected during hypoxia exposure (SMD −0.06; 95% CI: −0.23–0.11; p = 0.47). Acute exposure to hypoxia in controlled lab conditions appears to be detrimental to cognitive performance, specifically in reaction time, response accuracy, and memory.